Treatment of wide-based epiglottic cyst by microdebrider - Cheng-Ming Luo (Dove Medical Press, 2009)
Cheng-Ming Luo1,2, Shih-Wei Yang1,3, Tai-An Chen1,21Department of Otolaryngology - Head and Neck Surgery, Chang Gung Memorial Hospital, Keelung Taiwan; 2College of Medicine, Chang Gung University, Taoyuan, Taiwan; 3Graduate Institute of Clinical Medical Sciences, Chang Gung University College of Medicine, Taoyuan, TaiwanAbstract: Epiglottic cyst is not an unusual disease in the larynx. Although it is usually a benign lesion, airway problems may occur due to a large cyst. Surgical excision is usually the treatment of choice, with low recurrence. Because of the limited view and mobility of laryngoscopes, there is sometimes difficulty in the procedure of excision or marsupialization, especially in wide-based epiglottic cysts. The microdebrider has been widely used in treatment of otolaryngological diseases, and specialized blades were designed for laryngeal lesions. We report the use of a microdebrider for treatment of wide-based epiglottic cysts in six patients. The follow-up period ranged from five months to 62 months without recurrence. One hand-powered instrument provided a clear surgical field for precise removal of the cyst and synchronized suction, and increased mobility of the laryngoscope held in the other hand. In comparison to traditional microinstrumentation and carbon dioxide laser, the microdebrider offered a rapid and effective alternative in treatment of wide-based epiglottic cyst.Keywords: epiglottic cyst, microdebrider, laryngeal blade